Efeitos do uso de restrição de fluxo sanguíneo para ganhos de hipertrofia no treinamento resistido: uma revisão narrativa - Yoshida, Yoshimi Okawa (2024)
Currently, with the widespread adoption of the fitness lifestyle and the pursuit of a perfect body portrayed through social media, the quest for an aesthetic and muscular physique has become highly sought after in gym settings. Consequently, various training methods have been developed with the aim of improving muscle hypertrophy, such as vascular occlusion training, which seeks to block blood flow to the agonist muscle and promote greater hypertrophy. In this context, the present study aims, through a literature review, to and understand the effects of vascular occlusion training on resistance training-induced hypertrophy gains.